Concussion Surveillance: Do Low Concussion Rates in the Qatar Professional Football League Reflect a True Difference or Emphasize Challenges in Knowledge Translation?. Issue 1 (January 2015) - Eirale, Cristiano; Tol, Johannes L.; Targett, Steve; Holmich, Per; Chalabi, Hakim
Abstract : Objective: To investigate concussion epidemiology in the first football (soccer) division of Qatar. Design: Prospective cohort study. Setting: Professional First Division Football League of Qatar. Participants: All first team players were included at the beginning of each season. Interventions: Daily collection of training and match exposure from August 2008 until April 2012 by club medical staff. Head injuries during training and match play were recorded on standardized injury cards. Main Outcome Measures: Injury incidence was calculated as number of injuries per hour exposed to risk and expressed as rate per 1000 hours. Results: The incidence of concussions in professional club football in Qatar is 0.016 (0.000-0.033) per 1000 hours of exposure. Conclusions: The concussion incidence is only 25% of that in the previous European studies using the same time loss injury definition. This raises the possibility that concussions are underreported. Further research is necessary. In the meantime, concussion education of players, club medical, and support staff is warranted, in keeping with the Zurich concussion consensus call for the need for an increase in knowledge translation.